PENGEMBANGAN MEDIA AUDIO VISUAL (VIDEO) ANIMASI BERBASIS DORATOON PADA MATERI PELUANG UNTUK SISWA KELAS X SMA NEGERI 5 KUPANG - Liu, Ivoni Lazarina; Dao Samo, Damianus; Atrik Halim, Fransiska (Mandalika Mathematics and Educations Journal, 2025)
This study aims to produce Doratoon-based animated audio-visual media on probability material for Grade X students at SMA Negeri 5 Kupang that is valid, practical, and effective. The method used in this study is Research and Development with the ADDIE model, which consists of 5 stages: analysis, design, development, implementation, and evaluation. Data collection techniques and instruments used include interviews, questionnaires, and tests. The data analysis techniques employed are descriptive qualitative and quantitative analysis. The results showed that the Doratoon-based animation learning media on probability material met the criteria of being valid, practical, and effective. The feasibility of the learning media was obtained from the evaluation of three subject and media experts, with an average validity score of 4.67, categorized as valid. For practicality, the responses from small group participants averaged 4.37 and from large group participants 4.31, placing them in the practical category. Regarding effectiveness, the percentage of learning mastery in the small group was 100%, and in the large group, it was 74.19%, categorizing the learning media as effective. Thus, the developed learning media is valid, practical, and effective.